The Application of Photobiomodulation on Mesenchymal Stem Cells and its Potential Use for Tenocyte Differentiation - Roets, Brendon; Abrahamse, Heidi; Crous, Anine (Current Stem Cell Research & Therapy, 2025)
Tendinopathy is a prevalent and debilitating musculoskeletal disorder. Uncertainty remains regarding its pathophysiology, but it is believed to be a combination of inflammation, damage, degenerative changes, and unsuccessful repair mechanisms. Cell-based therapy is an emerging regenerative medicine modality that uses mesenchymal stem cells (MSCs), their progeny or exosomes to promote tendon healing and regeneration. It is based on the fact that MSCs can be differentiated into tenocytes, the major cell type within tendons, and facilitate tendon repair. Photobiomodulation (PBM) is a non-invasive and potentially promising therapeutic technique that utilizes low-level light to alter intracellular processes and promote tissue healing and regeneration. Recent studies have examined the potential for PBM to improve MSC therapy use in tendinopathy by promoting viability, proliferation, and differentiation. As well as enhance tendon regeneration. This review focuses on Photobiomodulation and MSC therapy applications in regenerative medicine and their potential for tendon tissue engineering.
Keywords: tissue engineering